Numerical and Experimental Study on Mixing Performances of Simple and Vortex Micro T-Mixers - Mubashshir Ahmad Ansari; Kwang-Yong Kim; Sun Min Kim (Micromachines, 2018)
Vortex flow increases the interface area of fluid streams by stretching along with providing continuous stirring action to the fluids in micromixers. In this study, experimental and numerical analyses on a design of micromixer that creates vortex flow were carried out, and the mixing performance was compared with a simple micro T-mixer. In the vortex micro T-mixer, the height of the inlet channels is half of the height of the main mixing channel. The inlet channel connects to the main mixing channel (micromixer) at the one end at an offset position in a fashion that creates vortex flow. In the simple micro T-mixer, the height of the inlet channels is equal to the height of the channel after connection (main mixing channel). Mixing of fluids and flow field have been analyzed for Reynolds numbers in a range from 1–80. The study has been further extended to planar serpentine microchannels, which were combined with a simple and a vortex T-junction, to evaluate and verify their mixing performances. The mixing performance of the vortex T-mixer is higher than the simple T-mixer and significantly increases with the Reynolds number. The design is promising for efficiently increasing mixing simply at the T-junction and can be applied to all micromixers.